American Indian Inferiority in Hume's Second Enquiry. Issue 1 (March 2020) - Roberts, Rodney
Abstract : It is fairly well known that Hume added a footnote to his essay 'Of National Characters' in which he asserts that all non-white peoples are naturally inferior to white people. Subsequently, he revised the note to assert only that black people are naturally inferior to white people. But while the view expressed in this footnote has been described as 'shockingly bigoted', and even as his 'racial law, ' it is still commonly thought that in Hume's voluminous writings it is apparently just this single passage which is definitely racist in its import. My aim in this paper is to show how American Indians are thought to be naturally inferior to white people in An Enquiry Concerning the Principles of Morals . There are, therefore, passages in Hume's second Enquiry which are also definitely racist in their import.